Instagram’s Algorithm and Its Impact on Second Language Acquisition; A psychological Analysis (International Journal of Scientific Research in Science and Technology, 2024)
In the rapidly evolving digital age, the role of social media is no more a mere entertainment tool but serves as a powerful tool for various disciplines which also includes language use, blending global trends with local realities. This research focuses on one of the most used social media platforms among learners, Instagram and its impact on second language acquisition (SLA) among English language learners (ELL). Instagram is known for its varieties of content and reels, and its algorithms influenced by the search engine optimization technique. The learners are often being pushed into unrealistic language expectations and becoming a victim of online bullying. Additionally, certain factors such as online bullying, unrealistic expectations, and untrustworthy recommendations lead to traumatic barriers among the English learners. Language anxiety, low self-confidence, are the factors which can disrupt their language learning process. Thus, this study examines how Instagram, and its algorithm impacts on SLA and on the psyche of non native English learners. The study majorly focuses on the psychology behind reels, the content pattern, the urge of immediacy and instant gratification, as the hindrances faced by ELL as their progress in acquiring English as a second language.